(untitled) (Experimental biology, 2022)
The article considered the ability to grow mint mentha piperita and Agstache rugosa in laboratory conditions. The extraction of essential oil from Mint mentha piperita and Agastache rugosa and its chemical composition were determined. The amount of essential oil was studied using spectrophotometer and NMR spectroscopy methods. The essential oil of mentha piperita and Agastache rugosa Mint has been considered relatively. The quality, chemical composition, and physical parameters of mint essential oils were studied, and their differences were determined. The study of the relative physical and chemical composition of essential oils obtained from Mint mentha piperita and Agastache rugosa by NMR spectroscopy and spectrophotometry methods. Essential oil from Mint mentha piperita and Agastache rugosa can be used in everyday life and in industrial, agricultural, and medical industries. The amount of chemical compounds was determined on the scales of two types of mint Mentha piperita and Agastache rugosa: flavanoids, menthol, saponins, polysaccharides, coumarins, tannins. The composition of the essential oil was determined by methods of spectrophotometry, NMR spectroscopy. In this regard, the optical density of mint was determined by the method of spectrophotometry. Organoleptic parameters (surface, color, smell, taste) of the resulting.